2020
DOI: 10.3390/geosciences10080292
|View full text |Cite
|
Sign up to set email alerts
|

Wheel Load and Wheel Pass Frequency as Indicators for Soil Compaction Risk: A Four-Year Analysis of Traffic Intensity at Field Scale

Abstract: Avoiding soil compaction is one of the objectives to ensure sustainable agriculture. Subsoil compaction in particular can be irreversible. Frequent passages by (increasingly heavy) agricultural machinery are one trigger for compaction. The aim of this work is to map and analyze the extent of traffic intensity over four years. The analysis is made for complete seasons and individual operations. The traffic intensity is distinguished into areas with more than five wheel passes, more than 5 Mg and 3 Mg wheel load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 29 publications
0
40
0
1
Order By: Relevance
“…Since the proposed tool can reduce the in-field traveled distance and traffic intensity, it potentially can reduce the soil compaction risk in the field. Moreover, other factors also influence soil compaction, such as increasing soil organic matter [30,31], adequate crop rotation [2,32], types of soils [33], and contact pressure [14], which should be considered in assessing the soil compaction risk in the field.…”
Section: Technical Characteristics Of the Distributor Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the proposed tool can reduce the in-field traveled distance and traffic intensity, it potentially can reduce the soil compaction risk in the field. Moreover, other factors also influence soil compaction, such as increasing soil organic matter [30,31], adequate crop rotation [2,32], types of soils [33], and contact pressure [14], which should be considered in assessing the soil compaction risk in the field.…”
Section: Technical Characteristics Of the Distributor Valuesmentioning
confidence: 99%
“…The other regards the optimization of the routing of vehicles within the geometrically represented field. Concerning this problem, advanced methods based on combinatorial optimization have recently been introduced based on one or multiple optimization criteria that include the minimization of the total nonworking traveled distance [11], total operational time [12], and soil compaction risk [13,14]. All of these algorithms used the metaheuristic algorithms (i.e., Clarke-Wright savings algorithm [15,16], genetic algorithm [17,18], simulated annealing algorithm [6,19], ant colony algorithm [20,21]) to find optimal or near-optimal solutions in a reasonable time.…”
Section: Introductionmentioning
confidence: 99%
“…Field traffic for spraying and fertilizing were conducted in tramlines (semi-permanent lanes) with a distance of 27 m. All other field traffic activities were random. A detailed description and analysis of all field traffic activities and the used machinery is given by Augustin et al [50]. The headlands in the north and the south of the field were tilled with the chisel plough as used for the RT1 plot.…”
Section: Study Areamentioning
confidence: 99%
“…Conventional tillage (plowing), seedbed preparation and soil treatments where agricultural machines and devices move repeatedly across the field increase soil compaction [6,7]. Heavy agricultural machines damage soil aggregates, increase soil density and mois-ture content, and decrease soil porosity and permeability [8][9][10]. Already in the 1970s, Byszewski and Haman [11] demonstrated that field operations involving a tractor with a weight of more than 2 tons increased soil density from 1.57 to 1.68 g/cm −3 .…”
Section: Introductionmentioning
confidence: 99%
“…Already in the 1970s, Byszewski and Haman [11] demonstrated that field operations involving a tractor with a weight of more than 2 tons increased soil density from 1.57 to 1.68 g/cm −3 . The main factors that contribute to soil compaction are heavy wheel loads and the number of tractor passes in the field [9]. Soil compaction compromises aeration and the water-holding capacity of soil, and induces changes in its chemical and biological properties [12,13], leading to soil degradation and decreased crop yields [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%